My son my Savior [videorecording (DVD)] : Mary, mother of Jesus - Boettcher, Steven J.; Lonnquist, Janis; Marchiano, Bruce; Crade, Corrina (Boettcher/Trinklein Television, 2015)
My son, my savior imagines Mary's childhood, growing up in a strict Jewish household, celebrating the annual feasts such as passover and hearing the prophecies about a coming messiah who would redeem Israel. Little did she know the vital role she would play in the fulfillment of those prophecies. Using the Gospel accounts as its framework, we seen how Mary responded to the events of Jesus' life and how her understanding of Jesus' mission grew over time.